Determination of Beta-Carotene Content in Carrot-Fortified Snakehead Fish Pempek after Sequential Freezing–Thermal Treatment and Vacuum Packaging Using HPLC - Aldilla Sari Utami; Ahlam Inayatullah Badrul; Nia Boru Ritonga; Ira Gusti Riani; Muhammad Abdurrahman (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study evaluated the effect of carrot puree concentration on the final ?-carotene content of snakehead fish (Channa striata) pempek subjected to integrated freezing–thermal–vacuum processing. Four formulations were prepared with varying carrot concentrations (0 g, 150 g, 300 g, and 500 g). ?-Carotene was quantified using a validated HPLC-PDA method with a C18 column and detection at 450 nm. The calibration curve showed excellent linearity (R² = 0.9986), with calculated limits of detection (LOD) and quantification (LOQ) of 0.13 mg/L and 0.40 mg/L, respectively. The measured ?-carotene concentrations ranged from 0.27 to 0.67 mg/kg, with the highest value observed in the 500 g carrot formulation. Statistical analysis confirmed a significant effect of carrot concentration on ?-carotene content (p < 0.05), demonstrating a clear dose-dependent relationship. These findings support the application of carrot puree as a functional fortification ingredient in traditional fish-based products. Future studies may investigate optimized thermal conditions or protective strategies to further improve carotenoid stability during processing. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-being